INTEGRASI NILAI KEARIFAN LOKAL DALAM MEMBANGUN SOLIDARITAS SOSIAL DAN PEMBELAJARAN INKLUSIF DI LINGKUNGAN PENDIDIKAN - Saputri, Elma Lia; Atmadillah, Atmadillah; Ardiansyah, Ardiansyah; Reski, Nurul Muazzaza; Ramadhani, Fitria; Maulidiah, Resky; Ridwan, Ihwan; A. Hasdiansyah, A. Hasdiansyah (Media Literasi Indonesia, 2026)
This Community Service Program (PkM) aims to integrate the Pacce value as part of Bugis local wisdom in strengthening social solidarity and inclusive learning within educational settings. Pacce, which emphasizes empathy, social care, and responsibility toward others, is implemented in learning activities as an effort to reinforce humanistic and contextual character education. The program employed a participatory approach through four stages: preparation, implementation, evaluation, and reflection. The participants were secondary school students who were actively involved in value-based discussions, context-driven material delivery, and reflective learning experiences. The results indicate an increase in students’ understanding and awareness of the importance of empathy, cooperation, mutual respect, and acceptance of diversity in school life. The integration of Pacce values contributes to the creation of an inclusive learning climate and the strengthening of social relationships among students. The novelty of this program lies in the utilization of Pacce as a pedagogical framework for inclusive learning that not only functions as a local wisdom–based character education approach but also explicitly supports the achievement of the Sustainable Development Goals, particularly SDG 4 (quality and inclusive education) and SDG 16 (peace, justice, and strong social cohesion) within the educational context. This program provides both conceptual and practical contributions to the development of sustainable, culturally grounded character education and inclusive learning practices.